PELATIHAN PENGEMASAN PRODUK PANGAN DAN DIGITAL MARKETING UNTUK UMKM OLAHAN PISANG DI DESA BARENG, KECAMATAN SAWAHAN, KABUPATEN NGANJUK - Reny Nugraheni; Dianti Ias Oktaviasari; Mia Ashari Kurniasari; Ratna Frenty Nur Kalim (Adiba Aisha Amira, 2025)
Local food MSMEs have great potential to boost the community's economy, including in Bareng Village, Sawahan Subdistrict, Nganjuk Regency. However, limited knowledge about packaging standards, product legality, and digital marketing strategies poses a challenge in improving competitiveness. This community service activity aimed to provide training on standard-compliant food product packaging, PIRT and halal licensing, and digital marketing strategies. The implementation methods included lectures, hands-on practice, and mentoring for 40 banana-processing SME actors. Evaluation was conducted through pre-tests and post-tests, as well as practice observations. The results showed an increase in the average knowledge of participants regarding food labelling standards from 62% to 88%. Packaging skills improved significantly, from 17 participants (41.7%) who were capable before the training to 37 participants (93.3%) who were capable after the training. In terms of digital marketing, 35 participants (86.7%) successfully created business accounts on social media and marketplaces and were able to create simple promotional content. This activity is expected to be the first step in increasing the competitiveness of banana processing MSMEs in local and digital markets.